Photothermal Therapy Using Gold Nanorods and Near-Infrared Light in a Murine Melanoma Model Increases Survival and Decreases Tumor Volume. (21st August 2014) - Popp, Mary K.; Oubou, Imane; Shepherd, Colin; Nager, Zachary; Anderson, Courtney; Pagliaro, Len
Abstract : Photothermal therapy (PTT) treatments have shown strong potential in treating tumors through their ability to target destructive heat preferentially to tumor regions. In this paper we demonstrate that PTT in a murine melanoma model using gold nanorods (GNRs) and near-infrared (NIR) light decreases tumor volume and increases animal survival to an extent that is comparable to the current generation of melanoma drugs. GNRs, in particular, have shown a strong ability to reach ablative temperatures quickly in tumors when exposed to NIR light. The current research tests the efficacy of GNRs PTT in a difficult and fast growing murine melanoma model using a NIR light-emitting diode (LED) light source. LED light sources in the NIR spectrum could provide a safer and more practical approach to photothermal therapy than lasers. We also show that the LED light source can effectively and quickly heat in vitro and in vivo models to ablative temperatures when combined with GNRs. We anticipate that this approach could have significant implications for human cancer therapy.